STUDI PENGARUH TRUST, COMMITMENT, COMMUNICATION, CONFLICT HANDLING TERHADAP CUSTOMER LOYALTY DI BANK MANDIRI SURABAYA - Hadinata, Melisa (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
This study aims to to examine the impact of relationship marketingstrategy on customer loyalty, and identify and analyze the influence trust,commitment, communication, conflict handling, the customer loyalty in BankMandiri in Surabaya.The data used in this study is primary data obtained from the distributionof questionnaires. Respondents of the study were 130 bank customers in Surabayaself that have become customer for 2 years and have a high school education withthe last non-probability sampling technique of sampling. Data processing methodused is multiple linear regression models, the F test and t-test values with thewindows program SPSS 18.0From the results of the data processing and hypothesis testing can beconcluded that there are three variables that have a significant impact oncustomer loyalty variables that commitment, communication, conflict handling,and one variable has no significant impact on customer loyalty in Surabaya Bankis variable trust. The value of the effect on customer loyalty Trust of 0.023, theinfluence of commitment on customer loyalty is at 0.434, for the communicationvariables influence on customer loyalty value of 0.235, and for the handling of theconflict on the value of customer loyalty for its effect is 0.213. Based on thecoefficient of determination of the amount of variation in the variables of trust,commitment, communication, conflict management is jointly able to explain thevariation in the variables of customer loyalty at 65.5%, while 34.5% describedvariables or other factors outside the model does not studied.